Gender trouble in the church: promoting associational autonomy through ontological difference - Vorster, Janko (University of the Free State, 2023)
This dissertation investigates the complex interplay between a pluralistic, liberal, and democratic state's duty to maintain diversity and protect the identities of individuals and groups with irreconcilable worldviews, focusing on the intersection of transgender identity and religious associations. The study grapples with the challenges of defining key concepts in the discourse of religious rights and diversity within a liberal democracy, avoiding simplistic definitions. The examination reveals the limitations of the prevailing discourse, which often assumes a secular neutrality that overlooks religion's role in shaping communal identity. It also explores the nuances of transgender rights, recognizing the importance of gender identity while respecting the traditional perspectives within religious associations. International legal developments highlight the tension between advocating transgender rights and upholding the principles of liberal democracy, revealing potential biases within the Yogyakarta Principles. The study underscores that claims based on transgender identity are ontological rather than empirical scientific facts. In the context of religious employment exemptions, the doctrinal core approach is critiqued in favour of the organic or permeated ethos approach, which respects the communal perspective and substantive autonomy of religious associations. Hypothetical scenarios further emphasise the doctrinal core approach's inadequacy in addressing issues related to religious exemptions and discrimination involving transgender individuals. Overall, the dissertation calls for an inclusive and nuanced approach that upholds the ideals of freedom, democracy, and diversity, while emphasising the need to safeguard the rights and identities of both transgender individuals and religious groups within a pluralistic society.
Dissertation(LL.M.(Constitutional Law and Philosophy of Law))--University of the Free State, 2023
Keywords: Secular neutrality; religious associations; religious associational identity; religious rights; religious group rights; communal identity; religious associational autonomy; ontological diversity; human dignity; human dignity conflicts; gender identity; transgender identity; gender ideology; transgender rights; Yogyakarta Principles; doctrinal core approach; organic approach; permeated ethos approach